Koperasi Digital: Seberapa Penting dan Kesiapannya? - Made Susilawati (STIE Malangkucecwara, 2021)
The purpose of this study was to examine how urgent and ready to digitize cooperatives during and through the covid-19 pandemic. Data was collected through literature study, interviews, focus group discussions, and observations. The object of the research is social capital in cooperatives in a number of districts/cities in NTT Province. The research method uses a qualitative approach through a case study. The result of this study is that the social capital of commitment as a healthy, independent, and contemporary cooperative is a stimulant towards the cooperatives digitization. Cooperative social capital from the cultural dimension of adaptation to digitalization still needs to be strengthened by literacy, preparation of resources supported by security of funds and data, and commitment.